2019
DOI: 10.15448/1980-6108.2019.3.34267
|View full text |Cite
|
Sign up to set email alerts
|

Percepções de estudantes de enfermagem sobre práticas educativas em imunização de adultos com o uso de Simulação Clínica

Abstract: AIMS: To identify and compare the perceptions of students about educational practices in the teaching of immunization of adults.METHODS: Observational, descriptive, comparative, performed with nursing students. These students were allocated to two groups: traditional strategies group (dialogue and clinical simulation for skills training) and group associated with high fidelity clinical simulation. After receiving the interventions, the Portuguese version of the Educational Practices Questionnaire was applied.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
2
0
2
Order By: Relevance
“…These findings suggest that different teaching methods can be effective for the students, if carried out properly. Educational programs prepared by educators in a clear way and with well-defined methods can be effective in the students' cognitive development and self-confidence when faced with complex topics that demand specific knowledge and skills [8][9]11 . In the lectured class, the students' participation is fundamental and the professor is considered a knowledge facilitator; thus, this methodology establishes that the teacher presents the content in order to guide reflective thinking capable of questioning, analyzing and debating about the knowledge object 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that different teaching methods can be effective for the students, if carried out properly. Educational programs prepared by educators in a clear way and with well-defined methods can be effective in the students' cognitive development and self-confidence when faced with complex topics that demand specific knowledge and skills [8][9]11 . In the lectured class, the students' participation is fundamental and the professor is considered a knowledge facilitator; thus, this methodology establishes that the teacher presents the content in order to guide reflective thinking capable of questioning, analyzing and debating about the knowledge object 14 .…”
Section: Discussionmentioning
confidence: 99%
“…In this perspective, we know that a lectured class is of major importance when teaching students; however, the active methodology stimulates sharing knowledge and enhancing education, for example, clinical simulation [7][8][9] . Therefore, a number of authors have shown promising results from clinical simulation as a teaching strategy [9][10][11] ; however, it is still necessary to develop other studies that compare the effects of this method to traditional teaching, based on a lectured class 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Esses achados sugerem que diferentes métodos de ensino podem ser efetivos para os estudantes, se realizados adequadamente. Programas educacionais preparados por educadores de forma clara e com métodos bem definidos podem ser efetivos no desenvolvimento cognitivo e na autoconfiança do aluno diante de temáticas complexas que demandam conhecimentos e habilidades específicas [8][9]11 .…”
Section: /13 Discussãounclassified
“…Nessa perspectiva, sabe-se que a aula expositiva dialogada possui grande importância no ensino de alunos, entretanto, a metodologia ativa, a exemplo da simulação clínica, estimula compartilhar conhecimentos e potencializar a educação [7][8][9] . Assim, autores mostram resultados promissores da simulação clínica como estratégia de ensino [9][10][11] , mas ainda é necessário o desenvolvimento de outros estudos que comparem os efeitos desse método e do ensino tradicional, baseado na aula expositiva dialogada 11 .…”
Section: /13 Introduçãounclassified